2009
DOI: 10.1097/hjh.0b013e32832af679
|View full text |Cite
|
Sign up to set email alerts
|

Association between refractory hypertension and obstructive sleep apnea

Abstract: OSA and reduced REM sleep time are associated with increased odds of having RHT and, therefore, may play roles in its pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
1
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(39 citation statements)
references
References 40 publications
(56 reference statements)
3
30
1
5
Order By: Relevance
“…OSA may occur in Ͼ80% of patients with resistant hypertension. 2,4,19 For the first time, we report on patients with both resistant hypertension and OSA (8 with OSA syndrome and in 2 with mixed obstructive and central sleep apnea). In all of the patients the catheter-based therapy caused substantial and significant reductions in systolic and diastolic BPs.…”
Section: Witkowski Et Al Renal Denervation and Sleep Apnea 563mentioning
confidence: 99%
“…OSA may occur in Ͼ80% of patients with resistant hypertension. 2,4,19 For the first time, we report on patients with both resistant hypertension and OSA (8 with OSA syndrome and in 2 with mixed obstructive and central sleep apnea). In all of the patients the catheter-based therapy caused substantial and significant reductions in systolic and diastolic BPs.…”
Section: Witkowski Et Al Renal Denervation and Sleep Apnea 563mentioning
confidence: 99%
“…Ruttanaumpawan et al found that about half of their 42 therapy-resistant patients with hypertension were suffering from obstructive sleep apnea. 4 Of course, there is always the lingering possibility that the patients are just not ingesting their medicines, and novel strategies have been developed to deal with that issue. 5 The advent of devicerelated treatments has pretty well laid the issue of refractory hypertension to rest.…”
mentioning
confidence: 99%
“…Faccenda (68 пациентов), Dimsdale (39 пациентов), Barbe (55 пациентов), Pepperell (95 паци-ентов), Monasterio (125 пациентов), подтверждают связь между СОАС и развитием АГ. Доказано, что уже через неделю лечения СОАС методом постоянного положи-тельного давления в дыхательных путях (Constant Positive Airway Pressure, CPAP) наблюдается снижение как систолического, так и диастолического АД [36]. При-менение СИПАП-терапии у пациентов с СОАС значи-тельно снижает риск впервые возникшей АГ [37], в то время как за 12 лет наблюдения за пациентами с нор-мальным уровнем АД и СОАС существенно увеличивался риск развития АГ [38].…”
Section: Resistant Hypertension резистентная артериальная гипертензияunclassified